Level of satisfaction towards factors that influence the training program based on employees’ perception: a study at Putra Specialist Hospital (Melaka) Sdn. Bhd. / Siti Nurbaya Khairuddin - Khairuddin, Siti Nurbaya (2009)
As part of the university requirement, a research will be conduct to identify the matter regarding Human Resource in training. This research was conducted at Putra Specialist Hospital (PSHM) during practical training within five months. This study was directly giving the opportunities in understanding the training conducted at PSHM. Generally, training refers to a planned effort by a company to facilitate employees’ learning of job-related competencies. These competencies include knowledge, skills, or behaviors that are critical for successful job performance. In PSHM the internal training will be conducted twice every week. It is divided into three categories which are Continuing Employee Education (CEE), Continuing Medical Education (CME), and Continuing Nursing Education (CNE). According to Raymond A. Noe (2008) continuous learning requires employees to understand the entire work system including the relationship among their jobs, their work units, and the company. Internal training at PSHM is usually held at theatreatte room at eleventh floor of PSHM building. It will be held every Tuesday and Thursday at 2.30p.m to 3.30p.m. Trainee satisfaction towards the program provided can be measure throughout four factors; course content, trainer, venue and also the accommodation (foods).This research is valuable tools that help collecting the information needed to understand, evaluate, and enhance the training program provided by PSHM’s management. The satisfaction from the participants toward this program is very important in order to measure whether this program is worth to conduct or not. This research is only investigate the internal training that conducted by PSHM excluded the external training. It is due to the limited time and lack of external training information.